Practices in the maintenance of equipment of the Army Engineers in the Visayas - Jancilan, Juan S. (2004)
This investigations aimed at determining the practices in the maintenance of equipment of the Army Engineer in the Mindanao. Management practices in terms of preventive maintenance and repair maintenance and the factors that influence the existing management practices in the maintenance of equipment were presented. The dependent variables in this investigation were equipment maintenance practices of the Army engineers in terms of preventive maintenance and repair maintenance. The independent variables were respondent's rank (Major and up, 2nd Lieutenant to Captain, Sergeant to master Sergeant, or Private to Corpora;), current position/designation in the unit (Battalion Executive Officer, Maintenance/Logistics Officer, Company Commander/Officer-in-Charge, Company First Sergeant/Motor-pool Sergeant, or Maintenance Supervisor/Chief Mechanic), length of military service (1o years and below, or above 10 years), military schooling completed (BENCOC, AENCOC, EOBC, and EOAC), and unit assignment (512ECB, 534ECB, 547ECB, and ESBN). While moderator variables were commend emphasis, supervision, skills, motivation, management, and resources. The respondents of the investigation were the randomly selected twenty three (23) Officers and fifty one (51) Enlisted Personnel of the 555th Engineer Brigade, Philippine Army who are directly involved in the maintenance of equipment, which comprises 85% of the population. The data gathering instrument used in this study was a Likert type rating scale adopted from Organizational Maintenance manager's Guide of the Department of the Army, USA, which had previously been validated. The instrument consists of three parts: Part 1 deals on the Personal Data of Respondents; The focus of Part II deals on factors that influence the Prescribe management Practices in the Maintenance of Equipment. Descriptive and inferential analyses of data were conducted to determine the respondents' existing management practices and perception of maintenance management of equipment. The descriptive statistics used were mean and standard deviation. The inferential statistical tools were the t-test for independent samples, one way Analysis of Variance and Pearson r. Path analysis in correlation coefficients was utilized to show the order of priority among responses of the respondents. The major findings of the study are as follows: 1) Existing management practices of Army Engineers. Among the preventive maintenance practices of the Army, the following were "generally practiced" by the Army Engineers in the Mindanao: a). Sufficient time si provided for the preventive maintenance checks and services of equipment. b). Maintenance faults are promptly reported and corrected. c). Unit commanders are aware of and give emphasis on the preventive maintenance of equipment. d). Every equipment has designated operator/driver and assistant operator. e). Operators/drivers are trained to operate and maintain their respective equipment properly. f). Maintenance supervisors/motor-pool sergeants monitor and supervise the preventive maintenance operation of the equipment. g). maintenance personnel are given sufficient training on maintenance of equipment to upgrade their skills and capabilities. h). Maintenance personnel are provided with necessary tools, manuals, repair parts, facilities and time for the preventive maintenance of equipment. i). Lubrication and maintenance schedule of equipment such as change of oil, filters and cleaners are strictly followed. j). Safety practices are strictly observed during conduct of preventive maintenance of equipment. "Generally practiced" repair maintenance procedures: a). Proper procedures are being followed like cleaning the equipment and processing of necessary documents such as job orders and technical inspection prior to the repair of equipment. b). Mechanics used test, measurement and diagnostic equipment when diagnostic fault of equipment. c). Diagnosis of the fault of equipment is done by qualified/skilled of work. d). Maintenance personnel show initiative and are attentive to quality of work. e). Mechanics are provided with the necessary tool tests, maintenance manuals and time during the repair of equipment. f). Equipment deadline for parts are cleaned and properly maintained. g). Maintenance supervisors assign mechanics to perform repairs. h). Maintenance Officer/supervisor check repair to assure quality of work. i). Repairs are accomplished on site whenever possible. j). Motor-pool has sufficient tools and facilities for the maintenance and repair of equipment. k). Controlled cannibalism of parts from unserviceable equipment deadline for parts is strictly observed. l). Equipment failure due to negligence is promptly and properly replaced. m). Unrepairable damaged parts are promptly and properly replaced. n). Safety of personnel and equipment are given priority during maintenance and repair operation. 2. There was no significant difference in the existing practices of Army engineers in the maintenance of equipment when they were classified according to rank and position, however, there were significant differences in the existing management practices when respondents were classified as to length of service, military schooling, and unit assignment. 3. all of the identified maintenance factors significantly influence the existing management practices in the effective maintenance of equipment such as skills of personnel, existing good management practices, motivation, good command emphasis, supervision, and availability of resources of the unit.
Research Paper (PM 299-Research Methods in Public Administration). -- [Iloilo City-UPV-CM], February, 2004.